Genetic Polymorphism of Vitamin D Family Genes CYP2R1, CYP24A1, and CYP27B1 Are Associated With a High Risk of Non-alcoholic Fatty Liver Disease: A Case-Control Study - Wang, Minxian; Zhang, Ru; Wang, Min; Zhang, Liuxin; Ding, Yajie; Tang, Zongzhe; Wang, Hongliang; Zhang, Wei; Chen, Yue; Wang, Jie (Frontiers in Genetics, 2021)
Background: Previous studies have highlighted the important role of vitamin D and calcium pathway genes in immune modulation, cell differentiation and proliferation, and inflammation regulation, all closely implicated in the pathogenesis of NAFLD. Objective: To investigate whether 11 candidate single nucleotide polymorphisms (SNPs) in vitamin D and calcium pathway genes (CYP2R1, CYP24A1 and CYP27B1) are associated with the risk of NAFLD. Methods: In this case-control study, a total of 3023 subjects were enrolled, including 1114 NAFLD cases and 1909 controls. Eleven genetic variants in CYP2R1, CYP24A1 and CYP27B1 genes were genotyped. Logistic regression analysis was used to assess the effects of these variants on NAFLD risk. The functional annotations of positive SNPs were further evaluated by bioinformatics analysis. Results: After adjusting for age, gender and metabolic measures, we identified that CYP24A1 rs2296241 variant genotypes (recessive model: OR, 1.316; 95% CI, 1.048-1.653; P=0.018), rs2248359 variant genotypes (recessive model: OR, 1.315; 95% CI, 1.033-1.674; P=0.026) and CYP27B1 rs4646536 variant genotypes (additive model: OR, 1.147; 95% CI, 1.005-1.310; P=0.042) were associated with an elevated risk of NAFLD. In combined effects analysis, we found that NAFLD risk significantly increased among patients carrying more rs2296241-A, rs2248359-T and rs4646536-T alleles (Ptrend=0.049). Multivariate stepwise analysis indicated that age, visceral obesity, ALT, γ-GT, hypertriglyceridemia, hypertension, low HDL-C, hyperglycemia and unfavorable alleles were independent predictors of NAFLD (all P<0.05). The area under the receiver operating characteristic curve was 0.789 for all the above factors. Conclusions: The polymorphisms of vitamin family genes CYP24A1 (rs2296241, CYP24A1 and rs2248359) and CYP27B1 (rs4646536) were associated with NAFLD risk in Chinese Han population, which might provide new insight into NAFLD pathogenesis and tools for screening high-risk population. Key words: non-alcoholic fatty liver disease (NAFLD); cytochrome P450 family 24 subfamily A member 1 gene (CYP24A1); cytochrome P450 family 27 subfamily B member 1 gene (CYP27B1); Polymorphism; risk.